Synthesis and Isolation of Enantiomerically Enriched Cyclopenta[b]benzofurans Based on Products from Anodic Oxidation of 2, 4‐Dimethylphenol. Issue 22 (25th June 2015) - Mirion, Michael; Andernach, Lars; Stobe, Caroline; Barjau, Joaquin; Schollmeyer, Dieter; Opatz, Till; Lützen, Arne; Waldvogel, Siegfried R.
Abstract: The anodic treatment of 2, 4‐dimethylphenol offers a powerful and direct method for the construction of a dehydrotetramer with four contiguous stereocentres on a multigram scale. The installation of propellanes on this scaffold using enantiomerically pure carbonyl compounds leads to a mixture of diastereomers. This mixture is easily separable using standard chromatography and gives rise to optically pure cyclopenta[ b ]benzofurans which are important scaffolds in a variety of natural products. The synthesis is easy to perform and allows a reliable access to chiral compounds with very high enantiomeric excess. It was possible to determine the absolute configuration of these compounds by comparison of experimentally recorded and calculated VCD spectra of all enantiomers. Abstract : Starting from a simple phenol component an enantiomerically highly enriched pentacyclic spirolactone was obtained in three synthetic steps. The absolute configuration of the cyclopenta[ b ]benzofuran moiety with four countigous stereocenters was elucidated by combination of experimental and theoretical spectroscopy.